Análise metagenômica da comunidade de Bacteria e Archaea do esgoto bruto, de reatores UASB e dos efluentes das etapas de pós-tratamento da estação de tratamento de esgoto Arrudas, Belo Horizonte-MG - Diego Dias Fassarela Marquioli (2017)
The water is obtained for human use mainly from rivers and lakes, and after this returns polluted to receptor water bodies becoming a potential source of pathogens. With the increase of population density in urban centers, measures to optimize the sewage treatment have become a priority. Wastewater treatment plants (WWTPs) accelerate the clearance of sewage and UASB reactors are regarded as adequate presenting low cost and easy operation. However posttreatment systems are still required in order to safely direct the effluent to receptor water bodies. The dynamics of bacterial communities responsible for metabolizing organic matter inside these reactors are poorly understood. This study aimed to analyze the profile of the bacterial community associated with sewage before and after treatment using metagenomics. Forty effluent samples were collected at strategic locations of demonstration scale sewage treatment systems of the Arrudas WWTP, BH/MG. New generation sequencing based on hypervariable regions of 16S rDNA was used and the evaluation of microbial communities was conducted through comparison with the Silva v.123 database by employing the MOTHUR software. After grouping as operational taxonomic units (97% similarity) data was processed (R software). The relative abundance of Archaea diminished in the superior portions of UASB reactors and Bacteria prevailed in all analyzed communities. Proteobacteria (43%), Bacteroidetes (15%), Firmicutes (13%), and Euryarchaeota (6%) were the most abundant phyla. Only association was between nitrate and diversity (Shannon) was detected. Among fecal-oral transmissible pathogens Arcobacter should be highlighted. Our data raised some concern regarding the efficacy of the wastewater treatments evaluated.